2005
DOI: 10.1038/sj.bjc.6602679
|View full text |Cite
|
Sign up to set email alerts
|

T-cell responses to human papillomavirus type 16 among women with different grades of cervical neoplasia

Abstract: Infection with high-risk genital human papillomavirus (HPV) types is a major risk factor for the development of cervical intraepithelial neoplasia (CIN) and invasive cervical carcinoma. The design of effective immunotherapies requires a greater understanding of how HPV-specific T-cell responses are involved in disease clearance and/or progression. Here, we have investigated T-cell responses to five HPV16 proteins (E6, E7, E4, L1 and L2) in women with CIN or cervical carcinoma directly ex vivo. T-cell responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
46
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 56 publications
9
46
0
4
Order By: Relevance
“…These findings are similar to data reported in previous studies (36,37,43,44) in which healthy women were more likely to show positive Tcell proliferative responses to HPV16 compared to women with abnormal cervical cytology. In addition, our findings are also consistent with prior studies that have reported lymphoproliferative responses to HPV16 peptides to be correlated with current status of HPV infection (14).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings are similar to data reported in previous studies (36,37,43,44) in which healthy women were more likely to show positive Tcell proliferative responses to HPV16 compared to women with abnormal cervical cytology. In addition, our findings are also consistent with prior studies that have reported lymphoproliferative responses to HPV16 peptides to be correlated with current status of HPV infection (14).…”
Section: Discussionsupporting
confidence: 91%
“…As illustrated in Table 2, 47% (28/60) of HPV16-negative patients were positive "responders" to E6 compared to only 14% (2/14) of HPV16-positive patients, χ 2 (1) = 4.94, p < .03. This association was also observed for E7 [44][45][46][47][48][49][50][51][52][53][54][55][56][57] and L1 382-396 peptides, both χ 2 (1)s > 5.40, ps < .03.…”
Section: T-cell Response To Hpv-16 Peptides In Relation To Participansupporting
confidence: 59%
See 1 more Smart Citation
“…23 It has been suggested that the HPV 16 immune response is dependent on the dose of antigen, because the frequency of CD41 T-cell responses was higher in cervical cancer patients compared with high-grade CIN patients. 8,10 We previously found that high HPV mRNA expression is associated with worse survival. 23 Apparently, the stimulating effect of high levels of oncogene on tumor growth outweighs the possible effect on the immune system that could lead to reduced growth.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 In a minority of patients with high grade Cervical Intraepithelial Neoplasia (CIN) as well as in half of the cervical cancer patients a specific T-cell response to E6 and E7 can be detected. [8][9][10] Cell-surface expressed human histocompatibility leukocyte antigen (HLA) Class I and Class II molecules form the target molecules for CD81 cytotoxic T-cells and CD41 T-cells, respectively. HLA Class I molecules consist of a glycoprotein heavy chain and a b 2 -microglobulin (b 2 M) light chain.…”
mentioning
confidence: 99%